The Impact of Sustainable Policy on Financial Performance in the Romanian Banking System - Carmen GHELASE; Mihaela NECULITA; Arabela ICHIM (Annals of Dunarea de Jos University. Fascicle I : Economics and Applied Informatics, 2023)
Research on the relationship between sustainability and financial performance (expressed in specific profitability indicators, from the perspective of the 3 ESG factors) was carried out in the banking system. The abstract analyzes the effects of the 3 dimensions of sustainability (economic/environmental/social) on the financial performances of the first top 3 banks in the Romanian system, the market share in the banking sector being relevant and also taking into account the fact that the banks are the first to realize sustainability reports.